Voltage stabilizer of generator output through field current control using fuzzy logic - Valdez, Clara (2013)
This project is about to design and implementation of a fuzzy logic controller for regulating the output voltage of a generator through its field current. An automated fuzzy logic-based control strategy has been designed for controlling the generator voltage by varying the field current values. The fuzzy logic controller was controlling the difference between the immediate output voltage and the rate voltage of the generator as error variable. The controller make an intelligent decision on the amount of field current that should be applied to the generator in order to keep the output voltage at its rated value. This control algorithm was implemented by using Mamdani method. This project is implemented using Simulink Matlab. Based on the test results show the output voltage is in compliance with the voltage regulator